The Influence of the Job Creation Law Implementation and Work Motivation on Employee Performance at CV Solfegio Music Pare - Bian Raharjo, Itot; Kusumaningrum, Divi; Hadi Nugroho, Isfauzi (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This study aims to analyze the influence of the Job Creation Law implementation and work motivation on employee performance (both teaching and non-teaching staff) at CV Solfegio Music Pare. The research method employed is quantitative with an explanatory research approach. The population consists of all employees of CV Solfegio Music Pare, with a sample of 30 respondents selected using purposive sampling. Data were collected through questionnaires using a 5-point Likert scale. The data analysis techniques included validity and reliability tests, multiple linear regression, and hypothesis testing. The results indicate that the implementation of the Job Creation Law has a positive and significant effect on employee performance (β = 0.312; p = 0.021). Work motivation also shows a positive and significant effect on employee performance (β = 0.476; p = 0.004). The coefficient of determination (R²) is 0.63, meaning that 63% of the variation in employee performance is explained by the implementation of the Job Creation Law and work motivation. Thus, it can be concluded that the combination of adaptive labor regulations and effective work motivation can improve individual performance in creative work environments such as CV Solfegio Music Pare.